Assessment of Instability in Degenerative Lumbar Spondylolisthesis using the Standing and Supine Lateral Radiographs. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the percentage of slip difference using the standing and supine lateral radiographs in symptomatic degenerative lumbar Spondylolisthesis.Methods: This descriptive study was conducted in department of Spine surgery unit Hayat Abad Medical Complex Peshawar from 2nd January 2019 to 2nd December 2020.All adults patients of both gender with low backache due to degenerative Spondylolesthesis meeting the inclusion criteria were enrolled in this study. All patients underwent standing and supine lateral radiographs. Slip of Spondylolesthesis was calculated according to Dupuis technique. Percentage of slip on standing radiographs were compared with supine and p value calculated using student t test. P value